Improving The Ability To Write Personalized With Imagination Strategy In Class X Students Of SMK TPI Al Hasanah - Sukron Agus Hutagaol (Indonesian Journal of Education and Mathematical Science, 2020)
Imagination strategy is a learning strategy that aims to enable students to develop the ability to focus and reflect. The steps for applying the Imagination strategy begin with (1) introducing the tofik that will be discussed, (2) then assigning students to close their eyes, (3) doing warm-up exercises to open their "inner eye", (4) providing an image for them form, (5) providing regular intervals of silence so that students can construct their own visual images, (6) ending the image briefing and having students remember their images, (7) asking students to form small groups and share their experiences, then ask students to write down what they imagine. From the above discussion, it can be concluded that the use of imagination strategies can help students in producing literary works in the form of short stories